Follistatin Alleviates Synovitis and Articular Cartilage Degeneration Induced by Carrageenan - Jun Yamada; Kunikazu Tsuji; Kazumasa Miyatake; Yu Matsukura; Kahaer Abula; Makiko Inoue; Ichiro Sekiya; Takeshi Muneta (International Journal of Inflammation)
Activins are proinflammatory cytokines which belong to the TGFβ superfamily. Follistatin is an extracellular decoy receptor for activins. Since both activins and follistatin are expressed in articular cartilage, we hypothesized that activin-follistatin signaling participates in the process of joint inflammation and cartilage degeneration. To test this hypothesis, we examined the effects of follistatin in a carrageenan-induced mouse arthritis model. Synovitis induced by intra-articular injection of carrageenan was significantly alleviated by preinjection with follistatin. Macrophage infiltration into the synovial membrane was significantly reduced in the presence of follistatin. In addition, follistatin inhibited proteoglycan erosion induced by carrageenan in articular cartilage. These data indicate that activin-follistatin signaling is involved in joint inflammation and cartilage homeostasis. Our data suggest that follistatin can be a new therapeutic target for inflammation-induced articular cartilage degeneration.